PENGARUH PERSEPSI MANFAAT TERHADAP MINAT PENGGUNA PAYLATER DENGAN DAYA TARIK PROMOSI SEBAGAI VARIABEL MODERASI - Prajogo, Uke; Ashidiq, Shafa Adellia; Andiani, Lidia (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
This research aims to analyze and prove the influence of perceived benefit variables on Paylater user interest with promotional attractiveness as a moderating variable. It is hoped that the results of this research will be useful and contribute to business actors being able to manage and improve their business performance. The object of the research is young entrepreneurs who are members of ABM Preneur. The total population is 71 entrepreneurs. Meanwhile, the total sample was 60 respondents obtained based on the Slovin formula. The data in this research is primary data obtained through distributing questionnaires or questionnaires. Sampling used the stratified purposive random sampling method. The analysis tool uses Smart PLS 3. The results of this research show: 1. Perceived benefits have a positive and significant effect on interest in using Paylater. 2. Promotional attractiveness does not moderate the influence of perceived benefits on Paylater user interest.